Colour contrast and regulation of the long jump approach run - Theodorou, A.; Ioakimidou, E.; Kouris, P.; Panoutsakopoulos, V.; Smpokos, E. (Journal of Human Sport & Exercise, 2013)
Research has shown that visual perception of the take-off board and the subsequent regulation of the approach run occur 4-5 strides prior to take-off. Contrast in visual perception is determined by the difference in colour and occurs when a surface of one colour induces its antagonist colour in an adjoining surface. The aim of the present study was to investigate if colour contrast between the track surface and the board affects the stride regulation pattern at the long jump approach run. Four long jumpers performed long jumps in two different occasions: 6 from a runway track coloured blue, with a white take-off board and 6 from a modified yellow board. The runway was marked and the approach runs were recorded with a panning camera. Toe- board distance (TBD) for each support phase in every run-up and the percentage distribution of adjustment of the regulated strides was calculated. With the white take-off board, the average TBD variability reached its peak value (21.74cm) on the 5th stride from the board and at a distance of 9.77m from take-off point. With the yellow take-off board the average TBD variability culminated (24.80cm) on the 7th stride from the board and at a distance of 13.40m from take-off point. With the white board, 80% of the adjustment was distributed during the last two strides as opposed to 61% with the yellow board. When a take-off board of a colour complementary to the runway`s blue track surface is used, athletes initiated their regulation 2 strides earlier. This may be attributed to an enhanced visual perception of the approaching target allowing a more uniform distribution of adjustments during the last two strides of the approach.